Evaluación agronómica de dos sistemas agroforestales, con base cultivo de Cacao (Theobroma cacao L.) en Guamag-Yacu, cantón Echeandía, provincia Bolívar - Sánchez Espinoza, Freddy Temistocles (2017)
The teak was introduced approximately 400-600 years ago in Indonesia. It is a hard wood, resistant to the influences of sun and of the rain, and it is easy to work, for what is ideal for the industry of the piece of furniture, the naval industry and the sector of the construction. The fertilization produces several changes in the physiology of the trees like bigger growth of the shaft. The leaves increase their activity fotosintética, the trees can expand their canopy, or they can change the distribution of the products fotosintetic. The objectives outlined for this investigative project were: i) Evaluate the characteristic morphological dasométricas that develop the teak plants to the application of N-P-K. ii) Determine the appropriate dose of fertilization based on N-P-K, in the teak plantation. iii) Carry out an economic analysis cost/treatments. The Ríos County has great forest diversity of resources; however its administration and use is generally not very rational, due to different reasons, among one of them to that the producing deforest constantly without reforesting and then it is the defenseless floor before the environmental inclemency. In our means experience documented in determining fertilization dose for forest plantations doesn't exist, even for the biggest nutriments N, P and K. however are known that the agricultural floors are mainly deficit of N and P and those with pH smaller than 5, also present important deficiencies of macro and micro nutriments. This project was carried out in the sector Gramalote, canton Ventanas, County The Ríos. An experimental design of complete blocks was used at random with 3 treatments and 4 repetitions, the treatments were: T1: Teak + 300, 200 and 300 g of N-P-K; T2: Teak + 400, 200 and 300 g of N-P-K and T3: Teak + 500, 150 and 300 g of N-P-K. They were carried out variance analysis, Test of Tukey to 5%; correlation analysis and lineal regression, cost/treatments. The results were: The application of N-P - K, impacted significantly in the agronomic components and mainly in the commercial height of the teak plants evaluated in m. The biggest commercial height in the teak plants was evaluated when applying 500, 150 and 300 g of N-P-K (T3) with two applications, one to the beginning of the investigation and another to the 60 days with 7,94 m. The independent variables that increased the commercial height of the teak plants were total height from the plants to the 120 days, wide equatorial of the leaf to the 120 days and number of leaves to the 120 days. The smallest cost/ treatment one had in the T3: Teak + 500, 150 and 300 g of N-P-K with $. 71,92; while the biggest cost registered in the T1: 300, 200 and 300 g of N-P-K with $. 105,60. This investigative project, allowed improving the production and productivity significantly from the teak plants when validating the use and the appropriate dose of N-P-K like complementary fertilization for the cultivation in this ecological area agriculture.